PENYULUHAN GAYA HIDUP AKTIF SEBAGAI UPAYA PEMBENTUKAN PEER KONSELOR KESEHATAN UNTUK MENINGKATKAN UKS DI SMAN 11 BEKASI DALAM RANGKA MENDUKUNG TRANSFORMASI LAYANAN PRIMER - Agustina, Dwi; Sariana, Erna (Jurnal Pengabdian Masyarakat Fisioterapi dan Kesehatan Indonesia, 2025)
Background: To realize quality human resources, namely human resources who are physically, mentally and socially healthy and have optimal productivity, continuous efforts are needed to maintain and improve health in all areas, including in the school environment. From year to year, the number of high school students and equivalents shows a fairly high number. The results of a national survey show that elementary, junior high and high school children, both male and female, show a lack of vegetable and fruit consumption and consume unhealthy foods such as foods with flavorings, junk food or instant foods. In addition, there are also school children who smoke and consume alcohol and lack physical activity. For this reason, strategic efforts are needed so that schools can become a conducive environment for the formation and development of clean and healthy living behaviors. The focus of community service activities is to support School Health Efforts by forming peer counselors as those who are expected to accelerate the process of adopting Clean and Healthy Living Behaviors among students. For this reason, the first activity carried out is counseling on physical activity. Objectives: Recruiting peer counselors as agents of change/health cadres in the school environment who can encourage the formation of Clean and Healthy Living Behaviors and increase knowledge about physical activity. Method: The community service program was implemented on June 8, 2024. The activities carried out included problem identification and counseling. Results: The community service activity succeeded in recruiting 25 students as peer counselors and increasing knowledge about physical activity.